Online Course: Definition and Classification - N. V. Grechushkina (Высшее образование в России)
Online course study is relevant due to their active integration into higher education in Russia and the variety of ways they can be used to implement the concept of life-long education. With the development of e-pedagogy theoretical analysis of online courses as an educational resource becomes a matter of research interest and is the aim of this paper. We analyzed pedagogical scientific works to sum up the characteristic features of online courses, define the term “online course”, break online courses up into groups, describe them as a type or form of education. We suppose online course should be considered as an organized aim-directed educational process based on principles of e-pedagogy and supported by means of modern ICT; a complete, logically and structurally solid educational unit provided with a unique system of electronic means of training resources and means of monitoring. We have worked out a classification of online courses taking the following six criteria: pedagogical approach, interaction of students, period of study, organization, purpose of learning, access to the course. Types of online courses are grouped into categories based on the criteria. The types are catalogued and characterized in the descriptive part of the classification.